Theoretical Determination of Intensity of Satellite Structure of the Tungsten (W) Lα1, 2 X-Ray Spectrum - Anmol Garg,; Vipin Sharma,; Sameer Sinha,; Lalit Kr. Dwivedi, (International Journal of Scientific Research in Science and Technology, 2024)
The tungsten Lα1,2 x-ray spectrum contains anomalous satellite feature Lα', thus receiving special attention. The theoretical attempt at determining the intensity of this feature is highly discrepant from the experimental result. This discrepancy has been the subject of much discussion. In the present work it has been shown theoretically that by extending the Bohm-Pines Hamiltonian and using many-body theory, satellite intensity thus obtained is in good agreement with the experiment; hence resolving the discrepancy.
Keywords: Tungsten Lα1,2 X-ray spectrum; Satellite; Bohm-Pines Hamiltonian; Many-Body Theory; Bulk Plasmon; Surface Plasmon